1993
DOI: 10.1121/1.408178
|View full text |Cite
|
Sign up to set email alerts
|

A cross-linguistic investigation of locus equations as a phonetic descriptor for place of articulation

Abstract: A previous study [H. Sussman, H. McCaffrey, and S. Matthews, J. Acoust. Soc. Am. 90, 1309-1325 (1991)] of American English CV coarticulation showed a remarkably linear relationship between onset frequencies of F2 transitions, plotted on the y axis, in relation to the F2 midvowel "target" frequencies, plotted on the x axis, for CVC tokens with initial [b d g] and ten medial vowel contexts. Slope and y-intercept values of regression functions fit to these scatterplots ("locus equations") were shown to serve as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 16 publications
(19 reference statements)
3
60
0
5
Order By: Relevance
“…Regression line fits to these plots reveal a linear relationship between F2yowel and F2 ons ' The regression lines for different consonants, or the locus equations that represent them, may be characterized by their slopes and intercepts. It has been found that the locus equation lines for different stop consonants occupy distinct regions in slope-by-intercept space (at least, if they are based on productions of speakers of a single language; Sussman, Hoemeke, & Ahmed, 1993). Locus equations represent an invariant that is not found in a particular token utterance, but rather over sets of consonant-vowel (CV) syllables that share their initial consonant.…”
Section: Locus Equationsmentioning
confidence: 99%
“…Regression line fits to these plots reveal a linear relationship between F2yowel and F2 ons ' The regression lines for different consonants, or the locus equations that represent them, may be characterized by their slopes and intercepts. It has been found that the locus equation lines for different stop consonants occupy distinct regions in slope-by-intercept space (at least, if they are based on productions of speakers of a single language; Sussman, Hoemeke, & Ahmed, 1993). Locus equations represent an invariant that is not found in a particular token utterance, but rather over sets of consonant-vowel (CV) syllables that share their initial consonant.…”
Section: Locus Equationsmentioning
confidence: 99%
“…For technical reasons, F3 was unreliable in the Yanyuwa and Yindjibarndi data, and will therefore not be reported here for the six speakers involved. (14) Locus equations: Locus equations (Lindblom 1963, Sussman, Hoemeke & Ahmed 1993 are an attempt to quantify the F2 transition between the consonant and the vowel across a variety of vowel contexts. Locus equations aim to capture the 'average' amount of coarticulation between a given consonant and multiple vowel contexts.…”
Section: Duration and Formant Analysesmentioning
confidence: 99%
“…This orderly plot captures a higher order and emergentlike acoustic commonality-namely, a vowel normalization of the F2 transition within each stop place category. Higher order locus equation coefficients-slope and yintercept-when serving as predictor variables in a discriminant analysis, were shown to correctly classify labial, alveolar, and velar stop place of articulation with 100% accuracy (Sussman et al, 1991 the slope of the regression function is proportional to the extent ofCV coarticulation being used by the speaker (see Figure 10 in Sussman et al, 1993). The consistently linear scatterplots, as documented across languages, gender, and speaking conditions, have recently been interpreted as possibly serving a functional role in speech perception and the representational encoding (viz., mapping) of acoustic-based place of articulation categories (Sussman, Fruchter, & Cable, 1995).…”
mentioning
confidence: 99%